Resveratrol Contrasts LPA-Induced Ovarian Cancer Cell Migration and Platinum Resistance by Rescuing Hedgehog-Mediated Autophagy - Alessandra Ferraresi; Andrea Esposito; Carlo Girone; Letizia Vallino; Amreen Salwa; Ian Ghezzi; Suyanee Thongchot; Chiara Vidoni; Danny N. Dhanasekaran; Ciro Isidoro (Cells)
Background: Ovarian cancer progression and invasiveness are promoted by a range of soluble factors released by cancer cells and stromal cells within the tumor microenvironment. Our previous studies demonstrated that resveratrol (RV), a nutraceutical and caloric restriction mimetic with tumor-suppressive properties, counteracts cancer cell motility induced by stromal IL-6 by upregulating autophagy. Lysophosphatidic acid (LPA), a bioactive phospholipid that shows elevated levels in the tumor microenvironment and the ascites of ovarian cancers, stimulates the growth and tissue invasion of cancer cells. Whether LPA elicits these effects by inhibiting autophagy and through which pathway and whether RV can counteract the same remain obscure. Aims: To investigate the molecular pathways involved in LPA-induced ovarian cancer malignancy, particularly focusing on the role of autophagy, and the ability of RV to counteract LPA activity. Results: LPA stimulated while RV inhibited ovarian cancer cell migration. Transcriptomic and bioinformatic analyses showed an opposite regulation by LPA and RV of genes linked to epithelial-to-mesenchymal transition (EMT) and autophagy with involvement of the PI3K-AKT, JAK-STAT and Hedgehog (Hh) pathways. LPA upregulated the Hh and EMT members GLI1, BMI-1, SNAIL-1 and TWIST1 and inhibited autophagy, while RV did the opposite. Similar to the inhibitors of the Hh pathway, RV inhibited LPA-induced cancer cell migration and 3D growth of ovarian cancer cells. BMI-1 silencing prevented LPA-induced EMT, restored autophagy and hampered cell migration, resembling the effects of RV. TCGA data analyses indicated that patients with low expression of Hh/EMT-related genes together with active autophagy flux tended to have a better prognosis and this correlates with a more effective response to platinum therapy. In in vitro 3D spheroids, LPA upregulated BMI-1, downregulated autophagy and inhibited platinum toxicity while RV and Hh inhibitors restored autophagy and favored BAX-mediated cell death in response to platinum. Conclusions: By inhibiting the Hh pathway and restoration of autophagy, RV counteracts LPA-induced malignancy, supporting its inclusion in the therapy of ovarian cancer for limiting metastasis and chemoresistance.